The Effects of Motivation, Job Satisfaction, and Discipline on Employee Performance in the Production Department of PT. Intracawood Manufacturing Tarakan City - Cahyaningrum, Widyastuti; Ramlah, Ramlah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to demonstrate the impact of discipline, job happiness, and motivation on the performance of employees in the production department of PT. Intracawood Manufacturing Tarakan City. Quantitative study was conducted utilizing the survey approach. Data collecting approaches based on observation (questionnaire and interview). The research sample was selected using probability sampling. Simple random sampling was used to select 190 personnel from PT. Intracawood Manufacturing's production department in Tarakan City. Hypothesis testing were also performed using multiple regression analysis models and partial t-tests with the SPSS software. The results prove that discipline has a positive and significant effect on employee performance, meaning that the higher the level of discipline, the higher the employee performance, the higher the job satisfaction, the higher the employee performance, the higher the level of job satisfaction, the higher the employee performance, the higher the level of motivation, the higher the employee performance.